Proceedings of the 34th International Cosmic Ray Conference — PoS(ICRC2015) 2016
DOI: 10.22323/1.236.0768
|View full text |Cite
|
Sign up to set email alerts
|

The Denoised, Deconvolved, and Decomposed Fermi gamma-ray sky

Abstract: We analyze the 6.5 year all-sky data from the Fermi Large Area Telescope in the energy range 0.6-307.2 GeV. Raw count maps show a superposition of diffuse and point-like emission structures and are subject to shot noise and instrumental artifacts. Using the Denoising, Deconvolving, and Decomposing Photon Observations D 3 PO algorithm, we modeled the observed photon counts as the sum of a diffuse and a point-like photon flux, convolved with the instrumental beam and subject to Poissonian shot noise, without the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The "bubble-like" component showed prominently the Fermi-bubbles, as well as an puffed up version of the Galactic disc. This morphology, as well as the harder, power-law like spectrum indicates that this component is mostly due to inverse Compton up-scattering of photons by CR electrons, which predominantly occurs in the volume-dominating hot and dilute part of the ISM [41]. The Fermi bubbles are then just two giant outflows driven by the hot ISM and in particular the light CR content of it, as a number of authors already suggested [46,50].…”
Section: The Astrophysical Gamma Ray Skymentioning
confidence: 75%
See 4 more Smart Citations
“…The "bubble-like" component showed prominently the Fermi-bubbles, as well as an puffed up version of the Galactic disc. This morphology, as well as the harder, power-law like spectrum indicates that this component is mostly due to inverse Compton up-scattering of photons by CR electrons, which predominantly occurs in the volume-dominating hot and dilute part of the ISM [41]. The Fermi bubbles are then just two giant outflows driven by the hot ISM and in particular the light CR content of it, as a number of authors already suggested [46,50].…”
Section: The Astrophysical Gamma Ray Skymentioning
confidence: 75%
“…The result of this analysis showed "cloud-like" gamma-ray emission with a spatial morphology closely resembling that of Galactic dust maps derived from completely independent microwave [48] or far-infrared [49] observations. This, as well as the steep spectrum with a hint of a bump at GeV as typical for γ-rays from the decay of π 0 s indicates that the "cloud-like" component is mostly due to hadronic CR proton interactions in the denser parts of the ISM [41]. The "bubble-like" component showed prominently the Fermi-bubbles, as well as an puffed up version of the Galactic disc.…”
Section: The Astrophysical Gamma Ray Skymentioning
confidence: 83%
See 3 more Smart Citations